Salesforce certification : administrator and app builder course. (Packt Publishing, 2022)
A hands-on training course that will help you prepare and get Salesforce certified. About This Video Learn to add standard components to Lightning pages Learn to configure email alerts for workflow rules Understand the difference between data loader and import wizard In Detail This Salesforce certification training course is designed to ensure that you learn and master the concepts of being a Salesforce Administrator and App Builder. In this Salesforce training, you will learn how to configure Salesforce to collect, analyze, and retrieve vital customer information and create applications using Salesforce Lightning. You will start by understanding exam details and the requirements. You will have an introduction to Salesforce and learn to create a Salesforce account. You will explore how to customize your profile and user as well as profile and role creation. You will be introduced to Salesforce data and how to create custom objects. Learn about access levels in OWD and permission sets. Along the course, you will learn Lightning app builder and Lightning components, and learn to create a Lightning homepage and record page. You will learn to demonstrate how to create various Lightning pages and how to send an HTML email from a Lightning app. Explore the various types of reports and create a custom report type, joined reports, and dashboards. By the end of this course, you will have understood the topics that will help you pass the certification exam. Audience This Salesforce certification training course is suitable for individuals looking to build a career in Salesforce, particularly app builders, developers, system administrators, sales representatives, IT managers, and product managers. Learners need to possess an undergraduate degree or a high school diploma. Professional experience with the basic concepts and functions of Salesforce--such as navigating Salesforce; data management and security; and using Sales Cloud--would be an advantage before taking the course or the exam.